Technical advance: The use of tree shrews as a model of pulmonary fibrosis. - Jennifer L Larson-Casey (Public Library of Science (PLoS), 2020)
Background Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive disease with a high morbidity and mortality. Some of the mechanisms of fibrosis development have been described using rodent models; however, the relevance of findings in these animal models is difficult to assess. New innovative models are needed that closely mimic IPF disease pathology. Methods To overcome this unmet need of investigating IPF with a relevant model, we utilized tree shrews, which are genetically, anatomically, and metabolically similar to primates and humans. Using human antibodies and primers, we investigated the role of macrophage phenotypic switching in normal and IPF subjects and bleomycin-injured tree shrews. Results Bronchoalveolar lavage (BAL) cells from tree shrews expressed human markers, and there was recruitment of monocyte-derived macrophages (MDMs) to the lung in IPF subjects and bleomycin-injured tree shrews. MDMs were polarized to a profibrotic phenotype in IPF and in bleomycin-injured tree shrews. Resident alveolar macrophages (RAMs) expressed proinflammatory markers regardless of bleomycin exposure. Tree shrews developed bleomycin-induced pulmonary fibrosis with architectural distortion in parenchyma and widespread collagen deposition. Conclusion The profibrotic polarization of macrophages has been demonstrated to be present in IPF subjects and in fibrotic mice. Although the lung macrophages have long been considered to be homogeneous, recent evidence indicates that these cells are heterogeneous during multiple chronic lung diseases. Here, we show new data that indicate a critical and essential role for macrophage-fibroblast crosstalk promoting fibroblast differentiation and collagen production. in the development and progression of fibrosis. The current data strongly suggest development of therapeutics that attenuate of the profibrotic activation of MDMs may mitigate macrophage-fibroblast interaction. These observations demonstrate that tree shrews are an ideal animal model to investigate the pathogenesis of IPF as they are genetically, anatomically, and metabolically closer to humans than the more commonly used rodent models.